Characteristic of Kimpul (Xanthosoma sagittifolium) Flour Modified with Hydrogen Rich Water - Gita Indah Budiarti; Endah Sulistiawati; Nurani Sofiana; Dessy Norma Yunita (Dept. of Chemical Engineering, Diponegoro University, 2021)
Kimpul one of tuber that potentially for substitute wheat in Indonesia. The disadvantage of kimpul tubers is that they are easily damaged or not durable because they have a high moisture content. Either method to modify starch is to use hydrogen rich water. The advantages of HRW compared to other modification methods are that HRW is safer, healthier for the body and more economical. The objective of the work was to determine the effect of hydrogen rich water and drying temperature on characteristic kimpul flour. Variables were used in this research pH (3, 6,7,9,11), soaking time (15, 30, 45, 60, and 75 minutes), temperature drying (100,110,120°C). The result is yield maximum obtained 38.67% at pH 7, soaking time 45 minutes and temperature drying 100°C. Swelling power is 0.52%. Structure molecule spherical and, separated. Result of proximate analysis for modified kimpul flour are ash content 4.49%; fat content 0.27%; fiber 4.69%; carbohydrate content 76.25%; protein 4.15%; moisture content 10.14%, energy 313.76 Kal/100 g; reducing sugar 0.78%. Color analysis result L, a and b are 19.63; 1.78 and 9.23 respectively. Hydrogen rich water has a good effect on molecules and color.Keywords: flour, kimpul, hydrogen rich water